1996
DOI: 10.1523/jneurosci.16-23-07599.1996
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent CNS Stem Cells Are Present in the Adult Mammalian Spinal Cord and Ventricular Neuroaxis

Abstract: Neural stem cells in the lateral ventricles of the adult mouse CNS participate in repopulation of forebrain structures in vivo and are amenable to in vitro expansion by epidermal growth factor (EGF). There have been no reports of stem cells in more caudal brain regions or in the spinal cord of adult mammals. In this study we found that although ineffective alone, EGF and basic fibroblast growth factor (bFGF) cooperated to induce the proliferation, self-renewal, and expansion of neural stem cells isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
726
1
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,119 publications
(763 citation statements)
references
References 33 publications
24
726
1
12
Order By: Relevance
“…36 In 1996, Reynolds and Weiss isolated neurosphereforming cells from the adult lateral ventricle and spinal cord. 37 The latter precursors required the combined effect of FGF-2 and EGF in order to proliferate however; precursors isolated from the lateral ventricles were EGF-dependent. This EGF dependency could be due to the presence of C cells and their immediate precursors in this particular region, a situation that is not seen at other sites.…”
Section: A Combination Of Dopamine Agonists Stimulates Proliferationmentioning
confidence: 99%
“…36 In 1996, Reynolds and Weiss isolated neurosphereforming cells from the adult lateral ventricle and spinal cord. 37 The latter precursors required the combined effect of FGF-2 and EGF in order to proliferate however; precursors isolated from the lateral ventricles were EGF-dependent. This EGF dependency could be due to the presence of C cells and their immediate precursors in this particular region, a situation that is not seen at other sites.…”
Section: A Combination Of Dopamine Agonists Stimulates Proliferationmentioning
confidence: 99%
“…4) it was demonstrated that these labeled cells, in vitro, under clonal conditions, can generate neurospheres that harbor astrocytes, oligodendrocytes, and neurons. They appeared to be CNS stem cells (Clarke et al, 1994;Weiss et al, 1996;Johansson, 2002). But what about the ependymal cells in the brain?…”
Section: The Function Of the Ependyma: A Concealed Reservoir Of Stemmentioning
confidence: 99%
“…In support of this viewpoint, coculture experiments have shown that ECs increase proliferation of NSPCs derived from the adult SVZ, thereby promoting neurogenesis [6,7]. However, accumulating evidence indicates that NSPCs are present in many parts of the adult brain, including the cortex [8][9][10], subcortical white matter [11], and spinal cord [12][13][14]; that is, outside conventional neurogenic zones, including SVZ and SGZ. Recently, we also found that NSPCs developed in the poststroke area of the cortex in the adult murine brain (ischemia-induced NSPCs) [8], and that ECs promoted the proliferation of these NSPCs, thereby enhancing neurogenesis after ischemia [15].…”
Section: Introductionmentioning
confidence: 99%